2008
DOI: 10.1128/jcm.01763-07
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of Mycobacteria by Raman Spectroscopy

Abstract: A number of rapid identification methods have been developed to improve the accuracy for diagnosis of tuberculosis and to speed up the presumptive identification of Mycobacterium species. Most of these methods have been validated for a limited group of microorganisms only. Here, Raman spectroscopy was compared to 16S rRNA sequencing for the identification of Mycobacterium tuberculosis complex strains and the most frequently found strains of nontuberculous mycobacteria (NTM). A total of 63 strains, belonging to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 17 publications
2
73
0
1
Order By: Relevance
“…This vibrational spectroscopy-based detection method can detect and differentiate various molecular compositions of microorganism [15][16][17][18] and therefore is suitable to identify the species and strains of microorganism. Buijtels technique is also are much faster; results can be obtained within 3 hours since positive automated cultured system is obtained [18]. In view of the importance of early diagnosis to prevent further spread of tuberculosis in the community, this time efficiency is the most significant contribution of Raman spectroscopy.…”
Section: Direct Detection Methodsmentioning
confidence: 99%
“…This vibrational spectroscopy-based detection method can detect and differentiate various molecular compositions of microorganism [15][16][17][18] and therefore is suitable to identify the species and strains of microorganism. Buijtels technique is also are much faster; results can be obtained within 3 hours since positive automated cultured system is obtained [18]. In view of the importance of early diagnosis to prevent further spread of tuberculosis in the community, this time efficiency is the most significant contribution of Raman spectroscopy.…”
Section: Direct Detection Methodsmentioning
confidence: 99%
“…A large set of techniques [1,2] was developed to access as much information as possible from samples. Among these, vibrational techniques [3,4,5] such as Infrared [3] and Raman spectroscopy [6] showed to be especially suitable for many applications due to their non-destructive and fast methodology [7,8]. Moreover, it has been shown that very reliable recognition results can be obtained without timeconsuming cultivation steps, since it is possible to extract informative spectra from single cells [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we have demonstrated that it is possible to study ergosterol metabolism in detail at the single cell level using fission yeast model. 8 Figure 3 shows the space-resolved lipid Raman spectra of S. pombe in mixed 12 C and 13 C isotope media. The band at 1602 cm -1 , corresponding to C=C-C=C symmetric stretch of the 5,7-diene structure of ergosterol in a pure 12 C medium redshifts to 1542 cm -1 in the 13 C medium.…”
Section: ·2 Single Cell Biochemistrymentioning
confidence: 99%
“…Raman spectroscopy, when combined with a microscope, achieves sub-μm spatial resolution, which can provide detailed spaceresolved molecular information and visualize their intracellular distribution. Owing to its ability to detect biochemical changes at the molecular level, Raman spectroscopy has gained much attention as a bio-analytical tool in recent years, and has been successfully applied in myriad different problems in biological and medical sciences, which include, but not limited to, structural identification and label-free biomolecular imaging of living cells, [1][2][3][4][5][6][7] cellular metabolic pathways, 8,9 cellular discrimination, [10][11][12][13] tissue characterization, 14,15 disease diagnosis, prognosis and therapy. component analysis (PCA) and clustering analysis (CA) are two popular methods.…”
Section: Introductionmentioning
confidence: 99%